12 PHORBOL ESTER-INDUCED ENDOTHELIAL CYTOSKELETAL REMODELING. (1st March 2006) - Bogatcheva, N. V.; Birukova, A.; Borbiev, T.; Kolosova, I.; Liu, F.; Garcia, J. G.N.; Verin, A. D.
Abstract : We have previously shown that treatment of bovine endothelial cell monolayers with phorbol myristate acetate leads to the thinning of cortical actin ring and rearrangement of the cytoskeleton into a grid-like structure, concomitant with the loss of endothelial barrier function. Here we demonstrate that phorbol myristate acetate induces both myosin and caldesmon redistribution from cortical ring into the grid-like network. However, the initial step of actin and myosin redistribution is not followed by caldesmon. Coimmunoprecipitation experiments revealed that short-term (5 minutes) treatment with phorbol ester leads to the weakening of caldesmon ability to bind actin and myosin. Prolonged incubation with phorbol myristate acetate, however, strengthens caldesmon complexes with actin and myosin, which correlates with the grid-like actin network formation. Phorbol ester stimulation leads to an immediate increase in caldesmon Ser/Thr phosphorylation. This process occurs at sites distinct from the sites specific for ERK1/2 phosphorylation and correlates with caldesmon dissociation from the actomyosin complex. Inhibition of ERK-kinase MEK fails to abolish grid-like structure formation, although reducing weakening of the cortical actin ring, whereas inhibition of protein kinase C reverses phorbol ester-induced cytoskeletal rearrangement. Our results suggest that protein kinase C-dependent phosphorylation of caldesmon is involved in phorbol ester-mediated complex cytoskeletal changes leading to the endothelial cell barrier compromise.